METHODOLOGICAL FOUNDATIONS OF STRATEGIC ANTI-CRISIS MANAGEMENT IN ENSURING ENTERPRISE STABILITY - ARIPOV Azizzhan Sakizhanovich («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
This article analyzes the methodological foundations of strategic anti-crisis management in ensuring enterprise stability. In the context of global economic instability, external economic threats, and internal resource constraints, comprehensive approaches aimed at early identification, assessment, and mitigation of crisis situations arising in enterprise operations are gaining increasing importance, including physical education and sports profile. The study develops an effective model of anti-crisis management based on the interrelation between the system, mechanisms, and processes of strategic management